Facebook and the diffusion of themes: Gender equality and female empowerment in the vision of korfball athletes - Silva, Renata Laudares; Tavares, Giselle Helena; Machado, Afonso Antônio (Revista Hipótese, 2022)
The role of Facebook in the dissemination of themes related to gender equality and female empowerment was analyzed, in the view of corfball athletes in Brazil. Qualitative study that used a questionnaire applied to 12 Korfball athletes from Brazil. Data were descriptively analyzed using the Content Analysis Technique. The results showed that the athletes have knowledge about gender issues and female empowerment in Korfball, they emphasized that Facebook is an important tool in the dissemination of the sport and the themes, gender equality and female empowerment of women in Korfball.